2013
DOI: 10.1007/s13365-013-0150-5
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines in CSF correlate with HIV-associated neurocognitive disorders in the post-HAART era in China

Abstract: In the current era of highly active antiretroviral therapy (HAART), the incidence of HIV dementia has declined, but the prevalence of HIV-associated neurocognitive disorder (HAND) remains high. HIV-induced systemic and localized inflammation is considered to be one of the mechanisms of HAND. Changes in cytokine levels in the cerebrospinal fluid (CSF) during HIV infection might help to identify HAND. To investigate whether the cytokine profile of the CSF during HIV infection could be used as a biomarker of HAND… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(87 citation statements)
references
References 26 publications
4
80
2
1
Order By: Relevance
“…In individuals who develop ANI and MND, markers of immune 65–67 and cytokine activation 68,69 are more pronounced than in HIV+ individuals without cognitive impairment. Likewise, changes in bioenergetics, as measured with neuroimaging 70–72 and metabolomic appraches 73,74 , are readily apparent in individuals with ANI or MND compared with cognitively normal HIV+ individuals, as are accumulations of bioactive lipids, such as ceramide, and sterol markers of cell stress 75,76 .…”
Section: Biomarkers In Handmentioning
confidence: 97%
“…In individuals who develop ANI and MND, markers of immune 65–67 and cytokine activation 68,69 are more pronounced than in HIV+ individuals without cognitive impairment. Likewise, changes in bioenergetics, as measured with neuroimaging 70–72 and metabolomic appraches 73,74 , are readily apparent in individuals with ANI or MND compared with cognitively normal HIV+ individuals, as are accumulations of bioactive lipids, such as ceramide, and sterol markers of cell stress 75,76 .…”
Section: Biomarkers In Handmentioning
confidence: 97%
“…Both MIP-1α and IL-8 are markers of inflammation in HIV infection and IL-8 has specifically been associated with ongoing inflammation in HIV+ individuals on HAART (Pierdominici, Giovannetti et al 2002; Letendre, Zheng et al 2011; Bastard, Soulie et al 2012; Mamik and Ghorpade 2014; Wada, Jacobson et al 2015). Additionally, CSF IL-8 correlates with HIV-associated neurocognitive disorders (Kamat, Lyons et al 2012; Yuan, Qiao et al 2013; Yuan, Liu et al 2015). …”
Section: Resultsmentioning
confidence: 99%
“…A separate study of individuals off cART identified increased inflammatory CSF IL-8, MCP-1, G-CSF, and IP-10 among those with cognitive impairment. (24…”
Section: Hand Pathophysiologymentioning
confidence: 99%